AN IMPROVED MODEL FOR STRUCTURAL TRANSFORMATIONS OF HEAT-TREATED ALUMINOUS DIOCTAHEDRAL 2:1 LAYER SILICATES - Drits V.A.; Besson G.; Muller F. (My University, 1995)
An improved model for the interpretation of thermal effects during dehydroxylation in alu- minous dioctahedral 2:1 layer phyllosilicates considers trans-vacant (tv) and cis-vacant (cv) 2:1 layers and leads to very different temperatures of dehydroxylation for these tv and cv vacant modifications. In particular, smectites and illites consisting ofcv 2:1 layers are characterized by dehydroxylated temperatures which are higher by 150"C to 200"C than those for the same minerals consisting of the tv 2:1 layers. A considerable lengthening of the OH-OH edges in cv 2:1 layers in comparison with the OH-OH edges in the tv 2:1 layers is postulated as the reason for the higher dehydroxylation. Dehydroxylation in aluminous cv 2:1 layer silicates should occur in two stages. Initially, each two adjacent OH groups are replaced by a residual oxygen atom and the A1 cations, which originally occupied cis -and trans-sites, become 5- and 6-coordinated, respectively. The structure of 2:1 layers corresponding to this stage of the dehydroxylation is unstable. Thus the AI cations migrate from the former trans-sites to vacant pentagonal prisms. The resulting dehydroxylated structure of the original cv 2:1 layers is similar to that of the former tv 2:1 layers. Diffraction and structural features of the cv dehydroxylates predicted by the model are in agreement with X-ray diffraction effects observed for cv illite, illite-smectite and montmorillonite samples heated to different temperatures. In particular, the diffusion of A1 cations to empty five-fold prisms during dehydroxylation of the tv 2:1 layers explains why dehydroxylation of reheated cv montmorillonites occurs at temperatures lower by 150"C to 200"C than samples that were not recycled.